Mofette Vegetation as an Indicator for Geogenic CO2 Emission: A Case Study on the Banks of the Laacher See Volcano, Vulkaneifel, Germany - Hardy Pfanz; Frank Saßmannshausen; Christiane Wittmann; Benny Pfanz; Annika Thomalla (Geofluids)
A geogenic CO2 emitting site (mofette U1) at the banks of the Laacher See, Eifel Mountains, was chosen to study the relationship between heavy postvolcanic soil degassing and vegetation during spring season. To test any interrelation between soil CO2 degassing and vegetation, soil chemism (pH, water content, conductivity, and humus content) and vegetation studies (number of species, plant-soil coverage) were performed. Geogenic soil degassing patterns of carbon dioxide and oxygen were clearly inhomogeneous, resembling soil porosity and distinct permeation channels within the soil. CO2 concentrations ranged from zero to 100%. Soil CO2 increased, while soil oxygen decreased with increasing soil depth. There was a reasonable correlation between CO2 degassing and soil pH as well as soil conductivity. Soil organic matter (SOM) resembled soil water distribution. The number of plant species (from a total of 69 species) as well as plant coverage strongly followed geogenic CO2 degassing. The total number of growing species was highest in low CO2 soils (max. 17 species per m2) and lowest at high CO2-emitting sites (one species per m2). Plant coverage followed the same pattern. Total plant coverage reached values of up to 84% in slightly degassing soils and only 5-6% on heavy CO2-venting sites. One plant species proved to be highly mofettophilic (marsh sedge, Carex acutiformis) and strictly grew on CO2 degassing sites. Most other species like grove windflower, spring fumewort, fig buttercup, wood bluegrass, addersmeat, and common snowberry showed a mofettophobic behavior and strictly avoided degassing areas. Specific plant species can thus be used to detect and monitor pre- or postvolcanic CO2 degassing.